Multiple endocrine neoplasia type 4: a new member of the MEN family - Singeisen, Hélène; Renzulli, Mariko Melanie; Pavlicek, Vojtech; Probst, Pascal; Hauswirth, Fabian; Muller, Markus K; Adamczyk, Magdalene; Weber, Achim; Kaderli, Reto Martin; Renzulli, Pietro (Endocrine Connections, 2023)
Objective Multiple endocrine neoplasia type 4 (MEN4) is caused by a CDKN1B germline mutation first described in 2006. Its estimated prevalence is less than one per million. The aim of this study was to define the disease characteristics. Methods A systematic review was performed according to the PRISMA 2020 criteria. A literature search from January 2006 to August 2022 was done using MEDLINE® and Web of ScienceTM. Results Forty-eight symptomatic patients fulfilled the pre-defined eligibility criteria. Twenty-eight different CDKN1B variants, mostly missense (21/48, 44%) and frameshift mutations (17/48, 35%), were reported. The majority of patients were women (36/48, 75%). Men became symptomatic at a median age of 32.5 years (range 10–68, mean 33.7 ± 23), whereas the same event was recorded for women at a median age of 49.5 years (range 5–76, mean 44.8 ± 19.9) (P  = 0.25). The most frequently affected endocrine organ was the parathyroid gland (36/48, 75%; uniglandular disease 31/36, 86%), followed by the pituitary gland (21/48, 44%; hormone-secreting 16/21, 76%), the endocrine pancreas (7/48, 15%), and the thyroid gland (4/48, 8%). Tumors of the adrenal glands and thymus were found in three and two patients, respectively. The presenting first endocrine pathology concerned the parathyroid (27/48, 56%) and the pituitary gland (11/48, 23%). There were one (27/48, 56%), two (13/48, 27%), three (3/48, 6%), or four (5/48, 10%) syn- or metachronously affected endocrine organs in a single patient, respectively. Conclusion MEN4 is an extremely rare disease, which most frequently affects women around 50 years of age. Primary hyperparathyroidism as a uniglandular disease is the leading pathology.